'That this too, too solid flesh would melt…': Necrogeography, gravestones, cemeteries, and deathscapes. (October 2018) - Nash, Alan
Physical geographers have long shown an interest in necrogeography – the spatial study of human burial practices (especially cemeteries, gravestones, and memorials) – to the extent that their study has informed investigations concerning processes of landscape change, biogeographic developments, or environmental alteration. This paper argues that such contributions can be enhanced if set within the wider study of the commemoration of death. Since the influential work of Philippe Ariès on Western attitudes towards death, scholars have been alerted to the physical implications of cultural changes in burial practices. Alternatively, others have more recently used the concept of the 'deathscape' to place such changes within their analyses. The paper concludes that physical geography's contribution to the study of necrogeography could be enhanced by the adoption of such broader frameworks.